2005
DOI: 10.1038/ni1194
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte arrest requires instantaneous induction of an extended LFA-1 conformation mediated by endothelium-bound chemokines

Abstract: It is widely believed that rolling lymphocytes require successive chemokine-induced signaling for lymphocyte function-associated antigen 1 (LFA-1) to achieve a threshold avidity that will mediate lymphocyte arrest. Using an in vivo model of lymphocyte arrest, we show here that LFA-1-mediated arrest of lymphocytes rolling on high endothelial venules bearing LFA-1 ligands and chemokines was abrupt. In vitro flow chamber models showed that endothelium-presented but not soluble chemokines triggered instantaneous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
410
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 355 publications
(441 citation statements)
references
References 48 publications
23
410
4
Order By: Relevance
“…6,7 In circulating leukocytes, LFA-1 remains largely inactive but becomes activated by endothelium-presented chemokines by signaling through G-protein-coupled receptors and application of shear stress, resulting in the extension of the molecule followed by immediate ligand binding. 8 The role of integrin activation in transendothelial migration has been widely studied. 9 Homing of DCs through the afferent lymphatics to the lymph nodes is still not completely understood and was assumed to passively follow the intrinsic flow of the lymph.…”
mentioning
confidence: 99%
“…6,7 In circulating leukocytes, LFA-1 remains largely inactive but becomes activated by endothelium-presented chemokines by signaling through G-protein-coupled receptors and application of shear stress, resulting in the extension of the molecule followed by immediate ligand binding. 8 The role of integrin activation in transendothelial migration has been widely studied. 9 Homing of DCs through the afferent lymphatics to the lymph nodes is still not completely understood and was assumed to passively follow the intrinsic flow of the lymph.…”
mentioning
confidence: 99%
“…In situ activation of the ␣␤ integrin heterodimer is rapidly triggered by the binding of specialized endothelial chemokines to G protein-coupled receptors (GPCRs) 3 (5)(6)(7)(8)(9). In vitro studies suggest that lymphocyte GPCRs such as CXCR4, CCR7 and CXCR3, when occupied by surface-presented rather than soluble ligands, can transmit a series of cytoplasmic signals that result in LFA-1 activation (8,10). This signaling occurs within subseconds through Gi heterotrimeric G protein activation.…”
mentioning
confidence: 99%
“…This signaling occurs within subseconds through Gi heterotrimeric G protein activation. A critical step in integrin activation is the almost instantaneous stabilization of an extended conformational state that must be rapidly coupled to the ligand-induced activation of the integrin headpiece (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CD11a (integrin alpha L, or Itgal ) heterodimerizes with the β2‐integrin CD18 to form LFA1. LFA1 interacts with ICAM‐1 and has roles in transendothelial migration, activation, and differentiation of lymphocytes 15, 16, 17, 18. We found that while CD11a is expressed on nearly all hematopoietic lineages, it is downregulated on HSCs 19.…”
Section: Introductionmentioning
confidence: 74%